Neuronal Surface Antibody-Medicated Autoimmune Encephalitis (Limbic Encephalitis) in China: A Multiple-Center, Retrospective Study - Shan, Wei; Yang, Huajun; Wang, Qun (Frontiers in Immunology, 2021)
Objective The epidemiological characteristics of patients with antibody-medicated autoimmune encephalitis in China remain unclear, and a large-scale epidemiological survey is necessary. Methods A multiple-center retrospective study was performed. We collected 1047 patients with suspected autoimmune encephalitis and ultimately enrolled 778 defined patients across centers in China. All patients were positive for serum (or cerebrospinal fluid [CSF]) antibodies. Demographic information and clinical data from January 2014 to January 2019 from 22 centers in China were reviewed. Results A total of 778 patients with autoimmune encephalitis were enrolled in the study. In general, the ratio of males to females was approximately 1.2:1. The main subtypes of autoimmune encephalitis were NMDAR-AE (61.35%), LGI-1-AE (20.61%), and GABAbR-AE (12.40%). According to the characteristics of age of onset, the incidence of autoimmune encephalitis showed a "double peak" distribution entailing a 20-year-old age group and a 60-year-old age group. We next analyzed the proportion of patients with tumors in this cohort. More specifically, there were 34 patients with tumors and 85 with tumor marker positivity. Relapse occurred in 81 patients within at least one year’s follow up study: 52 with NMDAR-AE (18.2%); 19 with LGI-1-AE (16.8%); 5 with GABAbR-AE (9%); and 3 with CASPR2-AE. Interpretation Due to the vast differences in demographic features, the incidence of cancer and the genetic characteristics between the populations in China and Western countries, the demographics, sex distribution, concomitant tumor rate, clinical features and relapse characteristics associated with autoimmune encephalitis in China shows a similar profile with Western countries with some minor differences.